The position of the principle of trust as the moral basis of partnership between the notary and the bank BPRS Bangkabelitung - Septa Tyana, Indah; Frengki Hardian; Mohammad Ryan Bakry (SEAN Institute, 2024)
This research focuses on the importance of agreements in business law, particularly partnership cooperation agreements. These agreements must comply with relevant regulations and often require the involvement of a Notary. The research methodology is normative juridical, combining practical implementation and library research to gather primary and secondary data. The study analyzes legal issues using statutory and conceptual approaches, emphasizing the validity and binding nature of partnership cooperation agreements. It also discusses the role of the Notary in crafting these agreements. Data analysis includes normative analysis and examination of the role of Notaries as the moral foundation in partnership with banks. The study also analyzes land ownership financing deeds in Bangka Belitung. The research findings indicate challenges in partnership agreements between Notaries/PPATs and banks, particularly in land ownership credit agreements. These agreements often favor the economically stronger party, typically the creditor. Communication issues between banks and customers, along with community factors related to home ownership credit transactions, present obstacles in implementing these agreements effectively.